Light Metals 2011 - Lindsay, Stephen (The Minerals, Metals & Materials Series, 2016)
The Light Metals symposia are a key part of the TMS Annual Meeting & Exhibition, presenting the most recent developments, discoveries, and practices in primary aluminum science and technology. Publishing the proceedings from these important symposia, the Light Metals volume has become the definitive reference in the field of aluminum production and related light metal technologies. Light Metals 2011 offers a mix of the latest scientific research findings and applied technology, covering alumina and bauxite, aluminum reduction technology, aluminum rolling, cast shop for aluminum production, electrode technology, and furnace efficiency.